The The Effect of Competency, Motivation and Discipline on Employee Performance: Regional Office VII of State Personel Agency Palembang - Nurhidayat, Nurhidayat; Asiati, Diah Isnaini; Choiriyah, choiriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to 1) determine the effect of Competence, Work Motivation, and Work Discipline on Employee Performance at Regional Office VII of the State Personnel Agency in Palembang 2) determine the effect of Competence on Employee Performance at Regional Office VII of the State Personnel Agency in Palembang 3) determine the effect of Work Motivation on Employee Performance at Regional Office VII of the State Personnel Agency in Palembang 4) determine the effect of Work Discipline on Employee Performance at Regional Office VII of the State Personnel Agency in Palembang. This type of research is Associative The variables used by researchers are the variables of competence, work motivation, work discipline, and employee performance The sample in this study was the Regional Office VII Employees of the Palembang State Civil Service Agency totaling 103 employees selected by Cluster Random Sampling The data used in this study were primary data with a questionnaire data collection method, The data analysis technique used was Multiple Emier Regression. The results of this study indicate that (1) competence, work motivation, and work discipline together have a positive and significant effect on employee performance (2) competence has a positive and significant effect on employee performance (3) work motivation has a positive and significant effect on employee performance (4) Work discipline has a positive and significant effect on employee performance